Pengaruh Kualitas Pelayanan Pajak, Pemeriksaan Pajak Dan Kepercayaan Wajib Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Orang Pribadi Pada Kantor Pelayanan Pajak Pratama Cileungsi Tahun 2019 – 2021 - Fajar Khoirul Anam; Ratih Kumala (Jurnal Ilmu Administrasi Publik, 2022)
The largest state revenue comes from taxes. The Directorate General of Taxes has well established a continuous development mission to meet the needs of the state through the government. So it is important for the Individual Taxpayer Compliance Level to be able to contribute to national development. The purpose of this study was to analyze the effect of tax service quality, tax audit, and taxpayer trust on the Individual Taxpayer Compliance Level at the Cileungsi Small Tax Office in 2019-2021. This study used a quantitative approach with a population of 100 respondents. Data collection used a questionnaire that has been tested for validity and reliability, and the data analysis used multiple linear analysis. The results of the t-test research on the tax service quality variable obtained a t-count value of 9.826 with a significance of 0.000. So it can be interpreted that there was a positive and significant effect of the tax service quality on Individual Taxpayer Compliance level. The results of the t-test on the tax audit variable obtained a t-count value of -0.272 with a significance of 0.787, there was no effect of tax audit on Individual Taxpayer Compliance level. The results of the t-test on the taxpayer trust variable obtained a t- count value of 8.727 with a significance of 0.000. Therefore, it can be interpreted that there was a positive and significant effect of taxpayer trust on Individual Taxpayer Compliance level. The tax service quality, tax audits, and taxpayer trust on Individual Taxpayer Compliance level obtained a value of f arithmetic 72.007 > f table 2.70 with a significance of 0.000 <0.05 it can be concluded that the tax service quality, tax audits, and taxpayer trust had a positive and significant effect on the Individual Taxpayer Compliance level.